Challenges for Nerve Repair Using Chitosan-Siloxane Hybrid Porous Scaffolds. (17th June 2014) - Shirosaki, Yuki; Hayakawa, Satoshi; Osaka, Akiyoshi; Lopes, Maria A.; Santos, José D.; Geuna, Stefano; Mauricio, Ana C.
Abstract : The treatment of peripheral nerve injuries remains one of the greatest challenges of neurosurgery, as functional recover is rarely satisfactory in these patients. Recently, biodegradable nerve guides have shown great potential for enhancing nerve regeneration. A major advantage of these nerve guides is that no foreign material remains after the device has fulfilled its task, which spares a second surgical intervention. Recently, we studied peripheral nerve regeneration using chitosan- γ -glycidoxypropyltrimethoxysilane (chitosan-GPTMS) porous hybrid membranes. In our studies, these porous membranes significantly improved nerve fiber regeneration and functional recovery in rat models of axonotmetic and neurotmetic sciatic nerve injuries. In particular, the number of regenerated myelinated nerve fibers and myelin thickness were significantly higher in rat treated with chitosan porous hybrid membranes, whether or not they were used in combination with mesenchymal stem cells isolated from the Wharton's jelly of the umbilical cord. In this review, we describe our findings on the use of chitosan-GPTMS hybrids for nerve regeneration.